2017
DOI: 10.1175/jpo-d-16-0108.1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Surface Wave–Current Interaction

Abstract: Wave–current interaction can result in significant inhomogeneities of the ocean surface wave field, including modulation of the spectrum, wave breaking rates, and wave statistics. This study presents novel airborne observations from two experiments: 1) the High-Resolution Air–Sea Interaction (HiRes) experiment, with measurements across an upwelling jet off the coast of Northern California, and 2) an experiment in the Gulf of Mexico with measurements of waves interacting with the Loop Current and associated edd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 77 publications
4
96
1
Order By: Relevance
“…Wave breaking variability due to wave‐current interactions was investigated with currents measured by HF radar. The results are qualitatively consistent with the measurements by Romero et al (), but the measurements exhibit substantially more variability at small scales, likely due to statistical sampling and submesoscale current variability not resolved by the HF radar.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Wave breaking variability due to wave‐current interactions was investigated with currents measured by HF radar. The results are qualitatively consistent with the measurements by Romero et al (), but the measurements exhibit substantially more variability at small scales, likely due to statistical sampling and submesoscale current variability not resolved by the HF radar.…”
Section: Discussionsupporting
confidence: 89%
“…The model solutions shown with thick lines where forced with homogeneous winds as opposed to those forced with relative winds (RW) shown with thick lines. For reference, see Λ( c ) sampling flight tracks in Romero et al (, Figure 7e).…”
Section: Resultsmentioning
confidence: 99%
“…The coupled model results were evaluated (Chen et al, ) by observations of surface waves and winds during hurricane Frances (2004). The observations of wave‐current interactions were collected by measuring winds, water levels, waves, and currents (Fewings et al, ; Hopkins et al, ; Lentz et al, ; Romero et al, ). Hopkins et al () concluded that the modulation of wave directions in shallow (2 and 7 m) water depths could reach 70° owing to the current‐induced refraction, based on a month of observations of wave directions and mean currents.…”
Section: Introductionmentioning
confidence: 99%
“…Refractions are triggered when waves propagate over spatially varying and strong currents [17,18]. Additionally, wave steepening can arise if the current direction is in contrast to the wave's direction [19]. The effect that tide and surge have on the wave must also be considered in numerical models, since the incident wave height increases during rising tides in the coastal zone [20].…”
Section: Introductionmentioning
confidence: 99%